Corrosion mitigation of CFRP-steel interface with sacrificial anodes. Issue 7 (3rd July 2019) - Kim, Yail J.; Chai, Yufei; Yoshitake, Isamu
ABSTRACT: This paper presents a corrosion mitigation scheme for steel members strengthened with carbon fiber reinforced polymer (CFRP) sheets. Of interest is the behavior of CFRP-steel interface with sacrificial anodes (zinc coins) that are in direct contact with the steel substrate. In accordance with electro-galvanism, accelerated corrosion testing is conducted to examine the effects of the sacrificial anodes on interfacial capacity, friction between the CFRP and corroded steel surface, and strain development along the interface. Ancillary tests indicate that the strength of the bonding agent and CFRP is not influenced by corrosion-conditioning, whereas the coefficient of friction increases with exposure time. Although the average corrosion rate of the interface slows down owing to the presence of the sacrificial anodes, this benefit diminishes as the anodes are consumed by free energy reductions in the zinc-steel galvanic couple. Under the progression of corrosion damage, the cases with the sacrificial anodes better preserve the interfacial capacity and demonstrate more stable responses than those without the anodes until CFRP-debonding failure takes place. An analytical model consisting of Markovian theory and Monte-Carlo simulation is developed to predict the capacity transition of the interface from one state to another. The concept of information entropy is taken to assess the resilience of the corrosion-damaged interface with the sacrificial anodes.